The Crime of Marital Rape Viewed from the Perspective of Criminal Law in Indonesia - Vernanda Ragil Saputra; Irfa Ronaboyd (Universitas Negeri Surabaya, 2025)
Marital Rape is a form of sexual violence against a wife or husband that occurs in a marital relationship. In general, sexual violence has been regulated in the construction of Indonesian criminal law, specifically (lex specialist) as outlined in Law Number 8 of 2004 concerning the Elimination of Domestic Violence (UU-PKDRT). However, it is necessary to develop subject qualifications in these regulations to emphasize the elements of marital rape so that the evidence obtained is more objective. This research aims to analyze the validity and proof of marital rape as a criminal offense of domestic violence. As normative research, this research uses a legal approach (statute approach) and a conceptual approach (on conceptual approach), using primary and secondary types of legal materials, and techniques for collecting legal materials using literature study using qualtatꬵ with analysis descriptive, based on the method A conclusion was found that, marital rape (rape within marriage) can be used as a type of criminal act of domestic violence if the evidence presented has been acknowledged, but the lack of evidence makes the proof process less objective.